Nano-titania doped with europium and neodymium showing simultaneous photoluminescent and photocatalytic behaviour - Tobaldi, D. M.
Titanium dioxide (TiO2) nanomaterials are attracting increasing interest, mostly because of their superior photocatalytic and antibacterial properties. In this work, we report the synthesis, by a \"green'' aqueous sol-gel route, of TiO2 doped with Eu and Nd (1 and 5 mol%), in order to extend its photocatalytic activity to the visible range, and also take advantage of the luminescent features of the rare earth metals (REs). Gels were dried in an oven at 75 degrees C, and then thermally treated at 450 degrees C in a static air flow furnace. Semi-quantitative phase composition (QPA) and microstructure (crystalline domain shape and size distribution) of the synthetic powders were studied by means of advanced X-ray methods: Rietveld refinements, and the whole powder pattern modelling (WPPM) technique, respectively. From these X-ray techniques, it was seen that the unit cell volume of RE-modified titania underwent a huge expansion, thus suggesting the incorporation of RE into the TiO2 lattice, accompanied by a decrease in the average crystalline domain diameters of anatase, rutile and brookite. The optical properties were also investigated by diffuse reflectance spectroscopy (DRS). Photoluminescent behaviour was assessed in the visible and near infra-red (NIR) spectral ranges. Photocatalytic activity of the samples was assessed both in liquid-solid and in gas-solid phases. The influence of the lighting conditions (UV- and visible-light exposure) was also taken into account for evaluating the photocatalytic activity. Nd-TiO2 was shown to be a bifunctional material, having both photocatalytic activity and NIR photoluminescent emission induced by the same excitation source, an unprecedented result.